IT TECHNOLOGIES AND DIGITALIZATION OF EDUCATION AS A FACTOR OF THE QUALITY OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN PHYSICAL CULTURE AND SPORTS (EDUCATION IN THE 21ST CENTURY, 2025)
Today's realities are the special attitude of the majority of teachers and students of education to the use of new information technologies, including their own electronic devices, during the educational process. Some of the subjects of the educational process believe that this has a positive effect on the quality of the provision of educational services, while others, on the contrary, have a negative attitude towards the modernization of the professional training of future specialists. This, in turn, actualizes the issue of digitalization of the educational process, in particular during the professional training of future physical culture and sports specialists.In order to find out the attitude of education seekers to the digitalization of the educational process of professional training of future specialists in physical culture and sports, the authors conducted a survey of students of the first (bachelor) level in the specialty 017 Physical culture and sports of the National University "Poltava Polytechnic named after Yury Kondratyuk". 187 students took part in the survey.The raised scientific question aroused the active interest of education seekers who passed a survey on the use of IT technologies in the professional training of future specialists, where, for the most part, they gave positive answers regarding the digitalization of the educational process.The authors single out the positive aspects of the digitalization of professional training of future physical culture and sports specialists and emphasize that we should not forget about the negative consequences of the digitalization of education and try to protect both students of higher education and teachers from them.It is concluded that the application of IT technologies, with the aim of digitalization of education during the professional training of future specialists in physical culture and sports, makes it possible to improve the educational process and ensure the quality of the provision of educational services.
Keywords: digitization of education; professional training; education seekers; specialists in physical education and sports; IT technologies